The integration of the authority of judicial institutions in solving general election problems in Indonesia - Ahmad Siboy (Legality : Jurnal Ilmiah Hukum, 2021)
The authority to adjudicate general election problems/ disputes scattered in various judicial institutions has made the resolution process drawn out and, complicated, creating overlapping powers and the potential for conflicting decisions between judicial institutions. This study examines how the judiciary's authority is regulated in adjudicating election problems, why it is necessary to integrate judicial authority, and how the concept of the judiciary's power is in judging all general election problems. This research aims to map the judiciary's power and find the judicial institution's design with an authority to adjudicate all general election problems. This study used juridical-normative research with a statutory approach, conceptual and case approaches. The results show that the authority to judge general election problems is given to the Constitutional Court, Supreme Court, State Administrative Court, and District Courts of Appeal. The large number of judicial institutions authorized to judge has been proven to be incompatible with general election administration and judicial power administration principles. The authority to adjudicate all election issues must be exercised in one judicial institution. The judiciary that can exercise this authority refers to the Constitutional Court, the Supreme Court, or the exercise can be performed by establishing a remarkable judicial institution.